2010
DOI: 10.4055/cios.2010.2.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hip Fractures in Jeju Island, South Korea: A Prospective Study (2002-2006)

Abstract: BackgroundThis study was perfomed to estimate the incidence of hip fractures of people older than 50 years in South Korea.MethodsInformation of patients over 50 years of age who had sustained a hip fracture were obtained from the records of eight hospitals in Jeju Island between 2002 and 2006 to calculate the incidence of hip fractures in this age group.ResultsThere were 820 hip fractures during the study period. The mean age of the patients at the time of fracture was 77.8 years (71.3 years in 181 men, 79.7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
2
24
1
1
Order By: Relevance
“…In contrast, studies in European cities12 and Canada11 reported that there were no associations between area level deprivation and mortality from fall injuries. In South Korea, senior citizens with a lower household income were reportedly more susceptible to fall related fatalities due to the increased risks from their residential conditions, with hazards such as steep street slopes, poorly designed stairs and slippery bathroom tiles 30. Other individual and geographic characteristics, including individual comorbidities, access to safety aids and access to appropriate facilities, might have contributed to the differences in fall mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies in European cities12 and Canada11 reported that there were no associations between area level deprivation and mortality from fall injuries. In South Korea, senior citizens with a lower household income were reportedly more susceptible to fall related fatalities due to the increased risks from their residential conditions, with hazards such as steep street slopes, poorly designed stairs and slippery bathroom tiles 30. Other individual and geographic characteristics, including individual comorbidities, access to safety aids and access to appropriate facilities, might have contributed to the differences in fall mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we performed a cohort study on hip fracture incidence in patients aged 50 yr or older who were admitted at eight hospitals of Jeju island for a hip fracture between January 2002 and December 2006 (11). Seven hundred and ninety patients with a diagnosis of femoral neck or intertrochanteric fracture were enrolled and followed (11).…”
Section: Introductionmentioning
confidence: 99%
“…Seven hundred and ninety patients with a diagnosis of femoral neck or intertrochanteric fracture were enrolled and followed (11). …”
Section: Introductionmentioning
confidence: 99%
“…Second, this study could not differentiate between the variety of pathologic fractures that can occur in the hips of the elderly, which could have led to our underestimating the incidence of fractures in this group. However, we previously validated these national claim data against a cohort study in Korea and found a sensitivity of 93 % and a positive predicted value of 77.4 % [40].…”
Section: Limitationsmentioning
confidence: 96%